"A Deed of the Darkest Violence": Rape and the Emergence of Sadism in Australian Psychiatry, 1920–1950. Issue 3 (3rd July 2022) - Bourke, Joanna
ABSTRACT: This article uses the sadist murder in 1937 of Dorothy May Everett in Newcastle (NSW) to reflect on sexual violence and psychiatry in Australia between the 1920s and the 1950s. Everett's murder incited debates about Australian masculinity, class, racial degeneration and sex crimes. It led to an unprecedented popular interest in the psychiatric diagnosis of "sadism". What do these sadistic rape-murders reveal about everyday constructions of the sexual sadist in Australia? How did people gain knowledge of perversions? Did psychiatric classification systems make a difference? Ian Hacking's concept of "making up" people is productive for reflecting on the spread of knowledge about psychiatric understandings of sexual violence.